Evaluation of genital self-image and sexual dysfunction in women with vulvar lichen planus or lichen sclerosus - Şükrü Yıldız; Hüseyin Cengiz; Cihan Kaya; İsmail Alay; Emine Öztürk; Aysun Fendal Tunca; Aliye Erdoğan; Levent Yaşar (Taylor & Francis Group, 2022)
Introduction Vulvar lichen planus (LP) and vulvar lichen sclerosus (LS) are chronic inflammatory diseases that affect women's sexual health. In this study, our aim was to investigate sexual function, anxiety level and genital self-image in vulvar LP and vulvar LS patients. Methods This study was conducted on a total of 178 women who presented to the gynecology clinic between February 2019 and January 2020. The patients were divided into the following groups: group 1, vulvar LP (n = 21); group 2, vulvar LS (n = 59); group 3, fungal vulvitis controls (n = 48); and group 4, healthy controls (n = 50). The validated Female Sexual Function Index (FSFI), Beck Anxiety Index (BAI), and Female Genital Self-Image Scale (FGSIS) questionnaires were assessed in all women. Results There were no significant differences among the groups with respect to age, parity, menopausal status, body mass index (BMI), vaginal intercourse past 1 month, marital status or educational status (p > .05). There were statistically significant differences between the vulvar LP and vulvar LS groups compared to control groups in terms of FSFI total scores and subscores (p < .001). When FGSIS and BAI scores were analyzed, significant statistical differences were found among the study groups (p < .001). A positive correlation was found between the FSFI and FGSIS scores in patients with vulvar LP and LS. Additionally, a negative correlation was found between the FSFI and BAI scores in patients with vulvar LP and LS. Conclusions Our study showed that sexual function, genital self-image and anxiety level were associated in vulvar LP and vulvar LS patients. Vulvar LP and vulvar LS patients with worse genital self-image have more sexual problems and anxious conditions.